2005
DOI: 10.1139/f04-179
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cumulative temperature as an initiating and terminating factor in downstream migratory behavior of Atlantic salmon (Salmo salar) smolts

Abstract: Temperature control of Atlantic salmon (Salmo salar) smolt migration was tested using a novel technique allowing nearly continuous monitoring of behavior with complete control over environmental conditions. Parr and presmolts were implanted with passive integrated transponder tags, placed in simulated streams, and monitored for upstream and downstream movements. Beginning 18 April, temperature was increased 1 °C every third day (advanced), fourth day (ambient), and tenth day (delayed). Smolt downstream movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
122
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 43 publications
11
122
2
Order By: Relevance
“…Models with ATU also consistently had lower AIC C scores than did the same model with temperature. This finding is in agreement with Zydlewski et al (2005), who found that in a controlled experiment, temperature experience was more relevant to both the initiation and termination of downstream movement of…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Models with ATU also consistently had lower AIC C scores than did the same model with temperature. This finding is in agreement with Zydlewski et al (2005), who found that in a controlled experiment, temperature experience was more relevant to both the initiation and termination of downstream movement of…”
supporting
confidence: 93%
“…Without the ability to control variables while manipulating others, it is difficult to assess their relative importance to the migration process. For example, Zydlewski et al (2005) experimentally manipulated temperature and found that cumulative temperature was more of a factor in initiating and terminating migration in Atlantic salmon than was a particular temperature threshold. However, other factors, such as increased flow, were not included in that study.…”
Section: Flow and Atumentioning
confidence: 99%
See 2 more Smart Citations
“…The timing of the onset and completion of the smolting process is governed by photoperiod and water temperature, respectively (Solbakken et al 1994;Handeland et al 2003;Zydlewski et al 2005), while water temperature and water flow are key factors for the initiation of seaward migration (McCormick and Saunders 1987;McCormick et al 1998). A successful sea entry presupposes that the completion of the smolt development is synchronised with the timing of migration.…”
mentioning
confidence: 99%